1956. godina naše ere: Vrhunac jugoslavenske vanjske politike - Jakovina, Tvrtko (2009)
The author argues that 1956, the year when the Yugoslav leader Josip Broz Tito met Nikita Khrushchev four times, talked with numerous leaders of the Third World and held a summit with G. A. Nasser and J. Nehru on Brijuni, together with the events in Hungary, was the year of largest Yugoslav foreign policy stretch. In spite of numerous indications that Yugoslavia would continue to move closer to the USSR, her policy remained “neutralist”, and not in dispute with the global interests of the West. This article is based on US, British and Yugoslav primary sources, oral history
Projekt MZOS
HRV